Mobility patterns across 42 NYC neighborhoods in four place categories. - Renquan Zhang (13167533) (2025)
Daily average visitor counts (in log scale) from home neighborhoods (y-axis) to destination neighborhoods (x-axis) in restaurants & bars (A), retail (B), arts & entertainment (C), and educational settings (D). The five boroughs of NYC (the Bronx, Brooklyn, Manhattan, Queens, and Staten Island) are indicated on top of each heatmap. Foot traffic data from January 6, 2020 to March 1, 2020 were used, representing the period before the implementation of governmental interventions. To avoid numerical issues for , we visualized the quantity , where is the daily average visitor count.